Development of model mesocycles of one - year training of young judokas in the first training year at the stage of primary training - Shatursunov, T. G. (Eurasian Journal of Sport Science, 2022)
Purpose: Experimental substantiation of the methodology for training young judokas of the first year training at the primary stage by introducing the developed 12 model mesocycles of one-year training.